The hybrid Public Service Announcement: implications of a rhetorical form - Rodenberg, Jesyca H. (Kansas State University, 2009)
Public Service Announcements are a fixture of both our media and cultural landscape. Their images and messages have inspired and defined movements and generations. The impact of PSAs is explored in this work to highlight the need to examine the impact of an emerging phenomenon of public service messaging: The Hybrid PSA. The Hybrid PSA is a message that blends and blurs the line between commercial and social causes. To explore the intricacies and impact of the Hybrid PSA, this work first works to define the “classical” PSA. Then, by observation and critique, the variance between the “classic” and the Hybrid is established. To contrast, the genre of Propaganda is explored and the possibility that the Hybrid PSA could be defined as propaganda is examined. Finally, the ethical implications of such a generic classification being established are discussed.
Keywords: Public Service Announcements; Propaganda; Ethics; Rhetoric; Language, Rhetoric and Composition (0681)